LIFE-CYCLE COST AS AN ASSESSMENT OF THE FINANCIAL EFFECTIVENESS OF AN INVESTMENT AND CONSTRUCTION PROJECT OF SOCIAL INFRASTRUCTURE - A. A. Kuznetsov (Вестник университета)
Original approach to assessment and evaluation of financial effectiveness of an investment project in state area via the life-cycle cost has been proposed. For long-term and capital-intensive projects, such as the construction of social infrastructure facilities with mixed public-private capital, the cost of the project life cycle, which expresses the material assessment of the costs of participants during the cycle of creation and maintenance of the construction object, is a complete and objective financial assessment of the project results, the effectiveness of which is determined by compliance with the target level. Knowledge of the full life-cycle cost in absolute and relative form, as well as its structure, enables execution of the project in the lowest cost form, thus ensuring the most effective investment decision. An economic and mathematical model for calculating the cost of life cycle costs in base and current prices, as well as an analysis of the factors forming it have been presented in the paper.